The Cost of Maternity Leave for the Orthopaedic Surgeon. Issue 22 (15th November 2020) - Nguyen, Cynthia V.; Luong, Marilan; Weiss, Jennifer M.; Hardesty, Christina; Karamitopoulos, Mara; Poon, Selina
Abstract : Introduction: Maternity leave among orthopaedic surgeons is not well understood. This study seeks to quantify past and current maternal leave characteristics of female orthopaedic surgeons. Methods: A survey was distributed to the members of the Ruth Jackson Orthopaedic Society and Women in Orthopaedics, an online group exclusive to female orthopaedic surgeons in practice or in training. The survey was open from April 2018 to October 2018 with access gained by way of a web-based link. Respondents were queried regarding demographics and maternity leave characteristics including age at conception, length of leave given/taken, and cost. Results: A total of 801 surveys were completed with 452 surveys returning with information regarding past pregnancies. Of the 452 surgeons with children, the average leave offered was 4.6 ± 4.2 weeks for the first child, with 8.2 ± 7.4 weeks taken. A difference was observed ( P < 0.001) between the amount of leave taken between residents (6.3 ± 5.0 weeks), fellows (8.3 ± 7.2 weeks), and practicing surgeons (9.6 ± 8.5 weeks). The average cost of the first leave was 40, 932 ± 61, 258. The average cost during training was different than during practice (154 versus 45, 350, P < 0.001). The length of leave offered ( P = 0.05) and taken ( P < 0.001) affects the cost, whereas delivery type, timing of stopping clinic, taking calls, and operating did not. Each additional week of leave offered saved a surgeon 2, 583, and each additional week taken cost 3, 252. Discussion: Residents take shorter leaves than fellows and attendings. The cost of taking leave is substantial, and the cost during practice is higher than during training. The amount of leave taken is greater than the amount of paid leave offered.